Socio-emotional wealth and successful generational transition in family business: the role of contextual factors. (26th May 2020) - Lazzarotti, Valentina; Minelli, Eliana Alessandra; Morelli, Chiara
This study aims to provide an innovative interpretation of the evolution of socio-emotional values and their impact on the generational transition. Based on the literature dealing with the socio-emotional wealth (SEW) theory and the evolution of SEW through the generations leading family firms (FFs), the study investigates the contextual conditions, respectively related to family and organisational factors, that interact with SEW and foster the shift to the new generation. The study investigates a sample of 15 family firms in which the generational transition has already taken place. In conclusion, the research supports the hypothesis of a link between the evolution of the young entrepreneurs' values and the successful generational transition and shows that it is not the level of the single socio-emotional component that matters, but rather the complex balance that is produced within each family business, thanks to the interaction between the role of the young entrepreneur on the one hand, and the family and organisational contexts on the other.